Sobre a noção de graça, pecado original e liberdade em Agostinho - SODRÉ, Alessandro (2024)
The existence of evil was a problem that tormented Augustine for a long time, as he wondered how it could be possible to reconcile the idea of a perfect God, who creates all good things, with the existence of evil. This could imply the imperfection of creation and of the Creator himself. To resolve this issue, the philosopher of Hippo turned to the doctrine of Original Sin and its consequences. This doctrine is directly linked to Augustine's conversion experience and his quest to understand the origin of evil. The elaboration of the doctrine of original sin allowed Augustine to express the dynamics of grace and break with pagan and Gnostic fatalism, as well as address issues related to evil, suffering, error, justice, and freedom. To defend his position, Augustine uses three main arguments: theological, patristic, and rational. Augustine argues that sin is a consequence of human free will and that human nature is inclined to sin due to the original fall of Adam and Eve. He maintains that human nature is essentially good, since it was created by God, but that it was corrupted by original sin. In this sense, Augustine asserts that man, in his state of sin, cannot do good without the divine aid of grace. Thus arises the need for grace, a special divine help adapted to the needs of fallen humanity, so that it can find its natural place again. Augustine finds support for his arguments in the Scriptures, especially in the letters of the apostle Paul; in the liturgy of the church, which prays for divine grace; and in the tradition of the apostolic fathers. Grace, for Augustine, is the divine indwelling in the human being, redirecting his love to God, to higher goods, and freeing him from selfish love. This indwelling occurs through the Holy Spirit, which is identified with the very love directed towards God. This operation in the human soul is divine grace, essential for overcoming sin and achieving good. In this way, Augustine not only responds to the criticisms and questions of his time but also offers a profound and articulated vision of human nature, sin, and grace, reaffirming the need for divine aid for man's salvation. In this scheme of sin and grace, Augustine does not eliminate human freedom. He understands man as possessing a free will, capable of choosing, and therefore deserving of just punishment for sins or reward for good works. However, for Augustine, true freedom is not merely the ability to choose, but rather the ability to do good and turn towards higher goods, towards God. The more human will subjects itself to divine grace, the healthier and truly free it becomes.